Mechanism of action of Butein in cutaneous squamous cell carcinoma through regulation of the TWEAK-FN14 signaling pathway - Dong, Qinyi; Zhang, Zijian; Li, Siying; Wang, Xinman; Zhang, Han; Bai, Jiahao; Zheng, Kaili; Liang, Lili (Frontiers in Oncology, 2025)
BackgroundThe incidence of cutaneous squamous cell carcinoma (cSCC) continues to rise, while current therapeutic approaches remain limited in efficacy for patients with advanced disease. The natural polyphenol Butein has demonstrated antitumor activity in various malignancies; however, its role and underlying mechanisms in cSCC remain unclear. Our previous study revealed that the TWEAK-FN14 axis promotes cSCC proliferation by activating the NF-κB and STAT3 pathways, whereas Butein can inhibit both pathways, suggesting that it may exert anti-cSCC effects by targeting the TWEAK-FN14 axis.ObjectiveTo investigate whether Butein affects cSCC growth by modulating the TWEAK-FN14 signaling pathway and its tumor microenvironment, and to elucidate the underlying molecular mechanisms.ResultsMolecular docking predicted that Butein exhibits strong binding affinity with TWEAK, FN14, cIAP1, and TRAF1/2 proteins, with binding energies ranging from −5.8 to −6.9 kcal/mol.In vitro experiments demonstrated that Butein inhibited the proliferation and migration of human cSCC cell line A431 with an IC50 of 43 μM and induced dose-dependent apoptosis. In a nude mouse xenograft model, treatment with Butein at 10, 20, and 40 mg/kg reduced tumor volume by 39.21%, 63.44%, and 79.05%, respectively, without affecting body weight. Mechanistic studies revealed that Butein markedly downregulated the protein and mRNA expression of TWEAK, FN14, and TRAF1/2 in tumor tissue, and decreased serum levels of NF-κB-related inflammatory factors, including IL-1β, IL-6, IFN-γ, and TNF-α.ConclusionButein effectively suppresses cSCC growth by directly binding to and inhibiting key proteins in the TWEAK-FN14 signaling pathway, thereby coordinately modulating the downstream inflammatory microenvironment. This study provides mechanistic insights and experimental evidence supporting Butein as a potential therapeutic candidate for cSCC.